International Relations and the Problem of Difference - Inayatullah, Naeem; Blaney, David L. (Routledge, 2004)
International Relations and the Problem of Difference has developed out of the sense that IR as a discipline does not assess the quality of cultural interactions that shape, and are shaped by, the changing structures and processes of the international system. In this work, the authors re-imagine IR as a uniquely placed site for the study of differences as organized explicitly around the exploration of the relation of wholes and parts and sameness and difference-and always the one in relation to the other. KM: Chapter 5 "Toward an Ethnological IPE" deals extensively with Polanyi's ideas
Keywords: economic anthropology; ethnological IPE; international political economy; international relations; political economy

Environmental Values in a Globalizing World: Nature, Justice and Governance - Lowe, Ian; Paavola, Jouni (Routledge, 2004)
This multidisciplinary volume presents a refreshing new approach to environmental values in the global age. it investigates the challenges that globalization poses to traditional environmental values in general as well as in politics and international governance.Divided into five parts, the book investigates how environmental values could be reconceived in a globalizing world.Part I explores contemporary environmental values and their implications for a globalizing world.Part II examines the development of Western and Eastern environmental valuesPart III discusses contemporary environmental politicsPart IV examines how values inform environmental governance and how governance solutions influence which values are realisedPart V concludes the volume with two different views of the prospects of environmental values in a globalising world. This study will be of great interest to students and researchers studying the environment in philosophy, political science, international relations, international environment law, environmental studies and development studies. KM - Contains chapter: "Global Liberalism, Environmentalism, and the Changing Boundaries of the Political : Karl Polanyi's Insights" by John M. Meyer
Keywords: MEYER, John M.; environmental policy; globalization; public policy

War and Social Change in Modern Europe: The Great Transformation Revisited - Halperin, Sandra (Cambridge University Press, 2004)
Halperin traces the persistence of traditional class structures during the development of industrial capitalism in Europe, and the way in which these structures shaped states and state behavior and generated conflict. She documents European conflicts between 1789 and 1914, including small and medium scale conflicts often ignored by researchers and links these conflicts to structures characteristic of industrial capitalist development in Europe before 1945. This book revisits the historical terrain of Karl Polanyi's The Great Transformation (1944), however, it argues that Polanyi's analysis is, in important ways, inaccurate and misleading. Ultimately, the book shows how and why the conflicts both culminated in the world wars and brought about a 'great transformation' in Europe. Its account of this period challenges not only Polanyi's analysis, but a variety of influential perspectives on nationalism, development, conflict, international systems change, and globalization.
Keywords: Europe; history; international relations; political science - history and theory

The Meaning of Freedom in a Complex Society: The Development of Karl Polanyi's Thought on Economics, Modernity, and Human Liberty - Katsh, Gabriel (Harvard University, 2004)
Keywords: freedom in a complex society

Desolation and Enlightenment: Political Knowledge After Total War, Totalitarianism, and the Holocaust - Katznelson, Ira (Columbia University Press, 2004)
During and especially after the Second World War, a group of leading scholars who had been perilously close to the war's devastation joined others fortunate enough to have been protected by distance in an effort to redefine and reinvigorate Western liberal ideals for a radically new age. Treating evil as an analytical category, they sought to discover the sources of twentieth-century horror and the potentialities of the modern state in the wake of western desolation. In the process, they devised strikingly new ways to understand politics, sociology and history that reverberate still. In this major intellectual history, Ira Katznelson examines the works of Hannah Arendt, Robert Dahl, Richard Hofstadter, Harold Lasswell, Charles Lindblom, Karl Polanyi, and David Truman, detailing their engagement with the larger project of reclaiming the West's moral bearing. In light of their epoch's calamities these intellectuals insisted that the tradition of Enlightenment thought required a new realism, a good deal of renovation, and much recommitment. This array of historians, political philosophers, and social scientists understood that a simple reassertion of liberal modernism had been made radically insufficient by the enormities and moral catastrophes of war, totalitarianism, and holocaust. Confronting their period's dashed hopes for reason and knowledge, they asked not just whether the Enlightenment should define modernity, but which Enlightenment we should wish to have. Decades later, in the midst of a new type of war and reanimated discussions of the concept of evil, we share no small stake in assessing their successes and limitations.
Keywords: ARENDT, Hannah; World War II; fascism; military history; political history; political philosophy; political theory; totalitarianism

Changing employment protection systems : Karl Polanyi's "Double Movement" and the evolution of federal labour standards in Australia 1979 to 2000 - Michelotti, Marco (Association of Industrial Relations Academics of Australia and New Zealand, 2004)
Yes
Keywords: Australia; double movement; industrial relations; labour standards

Globalization: People, Perspectives, and Progress - Mott, William H. (Greenwood Publishing Group, 2004)
This study expands the narrow economic-commercial focus of the topical media and places globalization in a multidisciplinary context as a continuing process and a permanent condition that transforms human living and society. Early chapters review the development of globalization as creating and diffusing knowledge, expanding people's perspectives on living, and continuing progress. These chapters introduce globalization as an iterative, human, and deliberate process of creating new knowledge and using it to reinterpret the world, time, and man's place in both. The later chapters present the major analytical perspectives of globalization--political, cultural, and economic--and a comparison of the primary carriers of globalism and barriers to globalization.Drawing on classical and modern analysis, as well as narrow, topical journalism, the work focuses each perspective on people through the human processes of creating knowledge and living together. The work expands the economic perspective beyond the fashionable focus on trade and investment into the triggering and shadowing relationships between economic growth, political conflict, and social stress. The political perspective expands international politics and law to global governance, triadic dispute resolution, and global civil society. The cultural and antiglobal perspectives reflect the success of economic globalization in bringing people directly into the narrowly rational processes of international politics and economics. The final analytical chapter collects and compares observations and develops conclusions about globalization across the several perspectives. Speculation about alterative futures for globalizing humanity can constitute a coherent standard, ideal, or direction for policymaking, or an agenda for continuing research and debate.
Keywords: comparative politics; political science; social science